Digital Analysis of the Dimensional Change Of an Irreversible Hydrocolloid Impression Material (Alginate) with Varying Storage Times. Issue 4 (December 2022) - Ibrahem, Fatemah; Giugliano, Thomas; Ruff, Ryan Richard; Choi, Mijin
Aim: The aim of this study was to digitally measure the dimensional changes in an irreversible hydrocolloid impression material (alginate) resulting from varying storage times under optimal storage conditions. Materials and methods: A single type V dental stone control cast was used to make 25 alginate impressions using perforated stock trays. The impressions were randomly assigned into five groups of five samples each (n=5 per group) with varying storage times: Group 1, poured at 15 minutes; Group 2, poured at one hour; Group 3, poured at 24 hours (one day); Group 4, poured at 72 hours (three days); Group 5, poured at 168 hours (seven days). All impressions were stored in sealed Ziploc® plastic bags with a wet paper towel (100% relative humidity) at room temperature and stored according to the assigned group storage times. All impressions were poured in type V dental stone according to the manufacturer's instructions. The casts were scanned with a digital 3D desktop scanner and saved as electronic stereolithography (.stl) files. Each .stl file of the scanned casts were superimposed on the .stl file of the control cast using Geomagic® Control X™ software. Three preselected fixed comparison measuring points (CMP) on each cast were compared to the control cast. Point one (CMP1) was on the midfacial surface of central incisor. Point two (CMP2) and point three (CMP3) were on the mesiobuccal proximal marginal ridge areas of third molars. The discrepancies between the files at each point were analysed with colour maps, and quantified (Table 1). The tolerance was set at ±10μm. CMP scores were analysed using one-way analysis of variance (ANOVA) and Kruskal-Wallis (K-W) non-parametric H tests. Results: Average gap distances across groups ranged from 0.04mm (seven-day group) to 0.06mm (one hour and 24-hour groups). Colour maps indicated increased dimensional change with increased storage time up to one day. After three days, shrinkage up to 139μm was measured. ANOVA results for CMP1 (F[4, 20] = 1.65, p = 0.020) and CMP3 (F[4, 20] = 0.44, p = −0.78) were not statistically significant. Similarly, K-W results for CMP2 were not significant (χ 2 = 3.62, p = 0.46). Conclusions: Under optimal storage conditions, there were no significant dimensional changes in casts poured from alginate up to seven days.